Assessment on a Dime: Low Cost User Data Collection for Assessment - Dillalogue, Eric; Koehn, Michael (Evidence Based Library and Information Practice)

(untitled) (University of Alberta Library, 2020)
Objective – This article describes the construction and use of a low cost tool for capturing user demographics in a physical library.Methods – At the Health Sciences Library of Columbia University Irving Medical Center, we created the Tap In/Tap Out tool to learn about the demographic details of our library visitors, such as their status, school affiliation, and department. The Tap In/Tap Out tool was implemented twice for two weeks in 2013 and 2017, with users voluntarily tapping their campus ID when entering and leaving the library. We checked campus ID numbers against university databases to fill in demographic details of the library users.Results – We constructed the Tap In/Tap Out tool using a Raspberry Pi and RFID card readers mounted on a foam board poster and placed near the library entrance. Participation in the Tap In/Tap Out tool ranged from 5-7% of the library gate count numbers during the survey periods. Though low, this participation provided a useful indication of user demographics that helped to strengthen library discussions with university administration. The 2013 survey results, which showed that the library space was actively used by students from all the constituent Medical Center schools, were used to support funding justifications. The 2017 survey results, which showed continued library usage, were used to illustrate the value of the library to the Medical Center community.Conclusion – The Tap In/Tap Out tool was inexpensive to implement and provided more information about library visitors than gate counts alone. Findings from the Tap In/Tap Out results were used to demonstrate library usage and justify funding. We describe how other libraries might create and implement the tool to capture greater levels of detail about the users visiting their spaces.